Photographic record of andean cat (Leopardus jacobita) in Salinas y Aguada Blanca National Reserve, Peru - Llerena-Reátegui, Gabriel (2017)
The Andean cat is a rarest wildcat of South America, categorized as Endangered by IUCN. Its habitat is in the high Andes of Argentina, Bolivia, Chile and Peru. In Peru, it has been reported in nine departments, and in four natural protected areas. We present two records from Salinas y Aguada Blanca National Reserve from early 2015, in two different locations. The first was near the Pillones village and the second near to Viscachani village; those are the first image record for Salinas y Aguada Blanca National Reserve; previous records were from skins and fecal DNA. Both records are the most recent from Peru and the very firsts complete images of full Andean cats live in the county.